Characterization of ridge gourd (Luffa acutangula) germplasm accessions for qualitative and seed quality traits - JHA, MONIKA; PANDEY, CHITHRA DEVI; SINGH, PRAVEEN KUMAR; ARCHAK, SUNIL; VERMA, MANJUSHA (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during summer seasons of 2021 and 2022 at ICAR-National Bureau of Plant Genetic Resources, New Delhi to evaluate 200 ridge gourd [Luffa acutangula (L.) Roxb.] germplasm accessions from India’s national genebank for 14 qualitative traits and three seed quality parameters. A significant level of diversity was observed in seed quality parameters (germination percentage and vigour index I) as well as qualitative traits (100-seed weight, early plant vigour, plant growth habit, fruit shape, ridge number and ridge pattern). All three fruit shapes, elongate, elliptical, and oblong were present in the germplasm, with 155 accessions showing continuous ridges numbering ten. Elongate shaped fruits at the marketable stage (83.5% of the accessions) with excellent ridge character make them visually appealing and well-suited to Indian conditions. Pearson’s correlation analysis revealed that germination percentage showed a significant positive correlation with vigour index and early plant vigour. Shannon diversity index pointed to the existence of phenotypic variation across traits, ranging from 0.31 (ridge number) to 2.06 (vigour index I). Traits such as vigour index I, germination percentage, 100-seed weight, early plant vigour, and plant growth habit demonstrated high diversity indices (>0.5). Accessions IC 352782, IC 353319, IC 338527 and IC 344351 were identified as superior for seed quality traits, exhibiting high germination percentage (>95%) and vigour index I (>1800) in comparison to checks. These four accessions are expected to be good starting points in the ridge gourd breeding programmes.